The first pterosaur 3-D egg: Implications for Pterodaustro guinazui nesting strategies, an Albian filter feeder pterosaur from central Argentina - Grellet Tinner, Gerald (2014)
The increasing number of fossil eggs of pterosaurs shed light on nesting environments and breeding behaviors of these extinct flying reptiles. Here we report the first partial three-dimensional egg of a pterosaur, Pterodaustro guinazui, from central Argentina. The specimen was discovered from the same Albian deposits as the exceptional P. guinazui embryo described in 2004. Microscopic characterizations indicate a pristine preservation of the 50 µm thick calcium carbonate, which differs significantly from the soft shell of Chinese pterosaur eggs. Estimate of the eggshell conductance implies that the nest had a minimum moisture content of 75%. This moisture estimate, combined with geological and taphonomical data, suggest that P. guinazui may have adopted a nesting strategy similar to those of grebes and flamingos rather than being buried on land, as previously hypothesized. Moreover, our results demonstrate that the nesting paleoenvironment of this pterosaur species was closely linked to a mesohaline lacustrine ecosystem in a basin governed by regional tectonic subsidence, a setting characteristic for the feeding and reproduction of modern flamingos.